Legal Conditions and Actual Needs in the Prevention and Treatment of Behavioral Addictions Related to the Use of Digital Technologies among Children and Adolescents - Łukaszuk, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The subject of behavioral addictions related to the use of digital technologies among children and adolescents is an intensifying phenomenon affecting increasingly younger users. However, the above issues in the sphere of institutional and legal changes remain new and require analysis. It is the duty of public authorities to provide children and young people with appropriate health care conditions, including in the sphere of mental health. Activities in the field of prevention and treatment of addictions of this kind should be treated with due seriousness, reflect the scale of the problem and, above all, meet the real needs in this matter.